Soft skills in engineeringg students, a comparative study - Rojas Gallo, Rodolfo (2020)
The present investigation, called Soft Skills in Engineering Students, a comparative study, 2020, aimed to describe, measure, and compare the level of soft skills in engineering students from two public universities in Lima, one named A and the other named B. The study was of a cross-sectional quantitative type of non-experimental design with a sample of 244 students from each university. A 22-question questionnaire was applied, validated by Claudet (2018), via online. His main results were that his students before University A have a relatively higher level in Assertiveness, Leadership and Communal Culture. This corroborates the working hypothesis.